2020
DOI: 10.3390/jcm9093015
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Orthopedic Treatment for Class III Malocclusion on Upper Airways: A Systematic Review and Meta-Analysis

Abstract: The aim of this systematic review is to compare the effect on the upper airways of orthopedic treatment for skeletal Class III malocclusion with untreated controls. Nine databases were searched up to August 2020 for randomized or nonrandomized clinical trials comparing orthopedic Class III treatment (facemask or chin-cup) to untreated Class III patients. After duplicate study selection, data extraction, and risk of bias assessment (Risk Of Bias In Non-randomized Studies-of Interventions [ROBINS-I]), random-eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
7
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 51 publications
4
7
0
4
Order By: Relevance
“…In the SA group with a higher level of maxillary protraction, AD1‐PNS, AD2‐PNS, PNS‐Ba and PNS‐Ho measurements increased in parallel with the skeletal measurements. In the literature, a mean of 2.1 mm in maxillary protraction with a face mask and in AD1‐PNS measurement has been associated with an average increase of 2.45 mm in AD2‐PNS 38 . Our study results indicated that a similar increase was observed in the RME and Alt‐RAMEC groups in AD1‐PNS, AD2‐PNS and PNS‐Ba measurements, whereas a higher than average increase was found in the SA group.…”
Section: Discussionsupporting
confidence: 77%
“…In the SA group with a higher level of maxillary protraction, AD1‐PNS, AD2‐PNS, PNS‐Ba and PNS‐Ho measurements increased in parallel with the skeletal measurements. In the literature, a mean of 2.1 mm in maxillary protraction with a face mask and in AD1‐PNS measurement has been associated with an average increase of 2.45 mm in AD2‐PNS 38 . Our study results indicated that a similar increase was observed in the RME and Alt‐RAMEC groups in AD1‐PNS, AD2‐PNS and PNS‐Ba measurements, whereas a higher than average increase was found in the SA group.…”
Section: Discussionsupporting
confidence: 77%
“…The sole included study assessing long-term status of treated Class II patients [35] indicated that not only were the benefits of functional appliance treatment retained 6 years afterwards, but a significantly greater post-treatment increase was seen. This is also consistent with previous evidence on the long-term stability of increased airway dimensions among patients with skeletal Class III treated orthopedically with maxillary protraction [55].…”
Section: Evidence In Contextsupporting
confidence: 92%
“…Maxillary deficiency in growing subjects, when left untreated, can lead to severe functional, aesthetic, breathing and psychological problems [ 1 , 2 , 3 , 4 , 5 , 6 ]. Important treatment goals in cleft patients are to establish a normal dental occlusion and to correct the skeletal discrepancy for psychological and functional well-being [ 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%